Acute fatty liver of pregnancy accompanied with disseminated intravascular coagulopathy and encephalopathy: A case report. Issue 10 (20th October 2022) - Qazi, Saba Saleem; Danish, Shiza; Akhai, Anusha; Khwaja, Hania; Tahir, Muhammad Junaid; Eljack, Mohammed Mahmmoud Fadelallah; Farooqui, Sabeeh Khawar; Asghar, Muhammad Sohaib
Abstract: Acute fatty liver disease of pregnancy (AFLP) is a rare condition associated with other common liver manifestations such as hemolysis, elevated liver enzymes, and low platelets syndrome (HELLP). We present a 27‐year‐old pregnant woman who developed hepatic encephalopathy and DIC after being diagnosed with Acute fatty liver disease of pregnancy. Abstract : To reduce mortality, early AFLP diagnosis and management are critical. Non‐specific symptoms include anorexia, abdominal pain, and vomiting. The liver biopsy is highly sensitive. LFTs, PT, PTT, ammonia levels, and hypoglycemia are all common findings.